The artistic expression of selected Chinese folk in Chen Gang’s violin worker - Yifeng, Zhang (2025)
Cheng Gang is a well-respected composer in China. His violin works are known for integrating Chinese folk music, yet the artistic characteristics of these folk elements have not been systematically examined. Most existing studies of his works focus on compositional style or national themes, with limited attention to artistic expression of Chinese folk music elements structurally and expressively embedded in violin works. Therefore, this study aims to investigate the artistic expression of Chinese folk music elements in the violin compositions of Chen Gang. It focuses on identifying the main features of folk music, including folk songs, minority music, opera music, folk stories, and Peking opera. It further analyzes how these elements are integrated into the musical structure and expressive techniques of the composer’s violin works. The study employed qualitative methods, including descriptive reviews, content analysis, and thematic analysis. Data were collected through interviews with 4 experts and 4 teachers, as well as a focus group with 14 students. The musical scores of five selected works, namely The Butterfly Lovers, Sunshine Over Tashkuergan, Morning in Miaoling, Wang Zhaojun and Tiger Kill, were also analyzed to identify folk music features, their structural integration and artistic expression, revealing their artistic and cultural significance. The findings reveal that Chen Gang systematically integrates folk music elements into his violin compositions through both structural and expressive techniques. These include the use of pentatonic scales, traditional rhythms, folk narratives, and operatic motifs, all of which enrich the emotional depth and cultural resonance of his works. The study contributes to the understanding of how Chinese folk music can be artistically expressed in Western instrumental forms. It advances theoretical discussions on musical hybridity and cultural preservation. Furthermore, it provides practical references for composers and performers seeking to integrate folk elements into contemporary music.